2001
DOI: 10.1080/713602840
|View full text |Cite
|
Sign up to set email alerts
|

Divalent cations in women with PCOS: implications for cardiovascular disease

Abstract: Polycystic ovary syndrome (PCOS) patients are known to have a high incidence of insulin resistance and glucose intolerance and tend to be at eventual high risk of hypertension, diabetes mellitus and cardiovascular disease. It has been repeatedly shown that a low serum ionized magnesium (Mg2+) and a high ionized calcium to magnesium (Ca2+/Mg2+) ratio is often associated with insulin resistance, cardiovascular problems, diabetes mellitus and hypertension. We were therefore interested in assessing the serum dival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…According, our electrophysiological data demonstrated that preincubation of 17␤-estradiol indeed induced a significant increase of TRPM6-mediated current. It is well known that estrogen can enhance Mg 2ϩ utilization and uptake (41,(45)(46)(47). In this line, Groenestege et al (9) demonstrated that the renal TRPM6 mRNA level in ovariectomized rats was significantly reduced, whereas 17␤-estradiol treatment normalized TRPM6 mRNA level, suggesting that estrogen can regulate Mg 2ϩ homeostasis via a transcriptional pathway.…”
Section: Discussionsupporting
confidence: 59%
“…According, our electrophysiological data demonstrated that preincubation of 17␤-estradiol indeed induced a significant increase of TRPM6-mediated current. It is well known that estrogen can enhance Mg 2ϩ utilization and uptake (41,(45)(46)(47). In this line, Groenestege et al (9) demonstrated that the renal TRPM6 mRNA level in ovariectomized rats was significantly reduced, whereas 17␤-estradiol treatment normalized TRPM6 mRNA level, suggesting that estrogen can regulate Mg 2ϩ homeostasis via a transcriptional pathway.…”
Section: Discussionsupporting
confidence: 59%
“…In the only other published study of magnesium levels and PCOS, Muneyyirci‐Delale et al (23) found small but statistically significant differences in both total and ionized magnesium levels among 25 women with PCOS compared to matched controls. Only 20% in that study were anovulatory, compared to 90% in our investigation.…”
Section: Discussionmentioning
confidence: 96%
“…A small ( n =25) study of women with PCOS who were overweight (mean BMI 29.5 kg/m 2 ) found significantly lower total and ionized magnesium levels in women with “signs and symptoms” of PCOS (primarily hyperandrogenism) compared to normal controls, but only 20% of these women were anovulatory. In addition, the study was probably underpowered to detect an association between magnesium levels and phenotypic manifestations of PCOS (power analysis not stated) (23).…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium intake from food sources has been found to have an inverse relationship with endometriosis [53]. One study found no difference in levels of total and ionized magnesium in endometriosis vs. control patients, though it was noted that participants in this study were taking various vitamin supplements [54]. Further studies are necessary to explore the role of magnesium in endometriosis further.…”
Section: Endometriosismentioning
confidence: 68%